1973
DOI: 10.1161/01.cir.48.1s3.iii-146
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass

Abstract: From October 1969 through March 1972, 1,276 patients underwent coronary artery bypass at the Texas Heart Institute. Associated conditions included simultaneous valve replacement and resection or repair of ventricular aneurysms or ascending aortic aneurysms. Among the series were 1,105 patients who underwent bypass surgery alone, with or without endarterectomy. Factors affecting outcome were analyzed and revealed adverse influences including concomitant endarterectomy, female sex, age, evidence of lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1974
1974
1978
1978

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
1
10
0
2
Order By: Relevance
“…This is also reflected in the results of the discriminant function analysis which show abnormal hemodynamic variables and only one 'classical' risk fac tor, hypertension, as a significant differentiating indicator. Similar find ings for the early mortality have been reported by Hall et al [7 ] and Loop et al [10].…”
Section: Discussionsupporting
confidence: 89%
“…This is also reflected in the results of the discriminant function analysis which show abnormal hemodynamic variables and only one 'classical' risk fac tor, hypertension, as a significant differentiating indicator. Similar find ings for the early mortality have been reported by Hall et al [7 ] and Loop et al [10].…”
Section: Discussionsupporting
confidence: 89%
“…Among our initial 2566 patients, the coronary score in survivors was 9.1 compared to 10.6 in patients who died. 17,19,32 Elevated Left Ventricular End-Diastolic Pressure and Dysfunction. Among our initial 2566 patients, left ventricular dysfunction and elevated left ventricular end-diastolic pressure (above 25 mmHg) was observed twice as often among patients who experienced early mortality.&dquo;, 12 Our more recent evaluation of the importance of left ventricular dysfunction has led us to modify somewhat our view of this risk factor.…”
Section: Risk Factorsmentioning
confidence: 99%
“…' Although the pathologic anatomy, physiology, and clinical manifestations were well described during the subsequent two centuries, it was exactly 200 years later that definitive anatomic, as opposed to symptomatic, treatment was implemented clinically by Favaloro and Effier3 at the Cleveland Clinic, and by Johnson and Leplet in Milwaukee. This significant breakthrough in the treatment of CAOD was preceded by a series of major developments,' including the discovery of blood groups by Landsteiner in 1901,~ development of techniques for blood vessel anastomoses by Carrel in 1906,' discovery of heparin by McLean in 1915,8 development of the concept of extracorporeal circulation by Gibbon in 1934,~ realization that autogenous tissue grafts would not result in rejection by Medawar in 1943,1° development of indirect myocardial revascularization by Vineberg in 1946,11 demonstration of the efficacy of hypothermia for myocardial preservation by Bigelow in 1950,12 application of selective coronary cinearteriography by Sones in 1962,13 and application of direct coronary artery bypass for congenital coronary anomalies by Cooley in 1963.14,15 Since the advent of direct coronary artery bypass (CAB) in 1968, the overwhelming preponderance of evidence has indicated that CAB is successful in relieving the symptoms of angina pectoris in 85-90% of patients [16][17][18][19] and that it does prolong life in patients treated surgically when compared to those receiving medical treatment alone.20-25 The degree to which CAB improves the ventricular function of the damaged myocardium remains controversial,28 but there is increasing evidence that CAB may also improve ventricular function and prolong survival in selected patien tS.21 .…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen patients died within the first 30 days after surgery (cumulative mortality, 3.9%). The remainder of the patients were followed up to five years after ACB.…”
Section: Mortalitymentioning
confidence: 99%